2015
DOI: 10.1097/rli.0000000000000156
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Adds Diagnostic Accuracy in Magnetic Resonance Neurography

Abstract: Diffusion tensor imaging has high diagnostic accuracy in peripheral neuropathy. Combining DTI with T2 can outperform T2-w imaging alone and provides added value in magnetic resonance neurography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 34 publications
(41 reference statements)
3
69
1
Order By: Relevance
“…First, no combination with diffusion imaging was established, which might have enhanced correct identification of nerves and accuracy, as suggested by investigations on peripheral nerve pathologies [18]. Second, we only enrolled healthy subjects in this study to establish a new quantitative MRN approach and to provide normative T2 values for clinical purposes; therefore, it has to be evaluated in further studies whether patients with lesions of LSP nerves show significantly altered measurements when compared to data derived from healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…First, no combination with diffusion imaging was established, which might have enhanced correct identification of nerves and accuracy, as suggested by investigations on peripheral nerve pathologies [18]. Second, we only enrolled healthy subjects in this study to establish a new quantitative MRN approach and to provide normative T2 values for clinical purposes; therefore, it has to be evaluated in further studies whether patients with lesions of LSP nerves show significantly altered measurements when compared to data derived from healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…136 As an additional functional technique, DTI is increasingly being investigated with regard to its potential to help detect nerve injury and monitor reinnervation. 137140 More recent work has shown that DTI can be used for diagnosis of neuropathy, 141 as well as bring new insights into the involvement of central nervous system in DPN.…”
Section: Non-invasive Mri Techniques To Assess Dpn Featuresmentioning
confidence: 99%
“…FA values are associated with the nerve development and brain functions [18][19][20]. The FA change rate could be a biomarker to monitor the brain development.…”
Section: Discussionmentioning
confidence: 99%